2011
DOI: 10.1016/j.ejcts.2011.04.014
|View full text |Cite|
|
Sign up to set email alerts
|

Bicuspid aortic valve leaflet morphology in relation to aortic root morphology: a study of 300 patients undergoing open-heart surgery

Abstract: In our study population, >50% of the patients admitted for surgery had a bicuspid valve. Aortic aneurysm was more common in BAV than in TAV patients. Aortic stenosis and aortic regurgitation were equally common in TAV and BAV with normal aortic dimensions, while aortic regurgitation was predominant in TAV with dilated aortas and aortic stenosis in BAV with dilated aortas. Dilatation of the aorta was similarly distributed regardless of BAV leaflet morphology. These findings support the idea of an intrinsic mech… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
86
1
1

Year Published

2011
2011
2023
2023

Publication Types

Select...
8

Relationship

4
4

Authors

Journals

citations
Cited by 68 publications
(90 citation statements)
references
References 24 publications
2
86
1
1
Order By: Relevance
“…BAV is the most common congenital cardiovascular malformation, with prevalence of 1-2%. Patients with BAV develop TAA at a younger age than patients with TAV and their aneurysms grow faster (1)(2)(3). The purpose of this study was to investigate the gene expression profiles associated with TAA formation in patients with BAV and TAV.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…BAV is the most common congenital cardiovascular malformation, with prevalence of 1-2%. Patients with BAV develop TAA at a younger age than patients with TAV and their aneurysms grow faster (1)(2)(3). The purpose of this study was to investigate the gene expression profiles associated with TAA formation in patients with BAV and TAV.…”
Section: Introductionmentioning
confidence: 99%
“…Another active point of discussion on the etiology of BAV is the question of hemodynamic alterations by the malformed aortic valve. It has been shown that BAV is associated with perturbed flow and hypothesized that this disturbance could result in disease de- 3 Johan Petrini, 4 Sanela Kurtovic, 1 Shohreh Maleki, 1 Maria J Eriksson, 4 Kenneth Caidahl, 4 Anders Hamsten, 1 Jean-Baptiste Michel, 5 Jan Liska, 3 Anders Gabrielsen, 2 Anders Franco-Cereceda, 3 and Per Eriksson Thoracic aortic aneurysm (TAA) is a common complication in patients with a bicuspid aortic valve (BAV), the most frequent congenital heart disorder. For unknown reasons TAA occurs at a younger age, with a higher frequency in BAV patients than in patients with a tricuspid aortic valve (TAV), resulting in an increased risk for aortic dissection and rupture.…”
Section: Introductionmentioning
confidence: 99%
“…These changes in the middle layer of the aortic wall lead to the development and expansion of the aortic aneurysm [1,4,11]. The incidence of TAAD in patients with BAV is estimated at about 30-40%, so it is three times higher than in patients with tricuspid valve, in which it is about 12% [1,3]. Aortic dissection is the most dangerous complication of BAV.…”
Section: Discussionmentioning
confidence: 99%
“…Its incidence in the general population is estimated at 1-2% [1,2]. There are 3 anatomical types of BAV: with a fusion of the right and left coronary leaflet responsible for 74% of all cases; with a fusion of the right and non-coronary leaflet (24%); and most rarely with a fusion of the left and non-coronary leaflet (2%) [3]. The consequence of BAV is its stenosis and/or regurgitation and the increased risk of infective endocarditis.…”
Section: Introductionmentioning
confidence: 99%
“…Aortic dilation (mainly involving the ascending aorta) is one of the most common non-valvular findings in BAV occurring in 35-80% of adult patients 3,4,19,37,38 . It is mainly asymptomatic and often precedes aortic dissection or rupture.…”
Section: Clinical Features Associated With Bavmentioning
confidence: 99%